Effects of Plantar Fasciitis on Health - Cheng, Guangxin; Yang, Hechong (Quality in Sport, 2024)
Purpose:Plantar fasciitis is a common condition.Despite the lack of a clear cause for this condition, it could be linked to excessive exercise and standing periods over time, as well as muscle strain from stress and obesity.This study aims to lower the prevalence of plantar fasciitis and enhance patients’ plantar function by comprehensively understanding the clinical symptoms, risk factors, diagnostic and treatment options, and the most recent information on prevention of plantar fasciitis. ln order to offer specific reference plans for the clinical treatment of individuals suffering from plantar fasciitis, with a focus on middle-aged and older patients as well as athletes. Methodology:There was a search conducted through PubMed, Embase, Web of Science, and the Cochrane Database of Systematic Reviews for published systematic reviews and meta-analyses up until February 25, 2024. Description of state of knowledge:The band of tissue known as the plantar fascia, which runs from the heel to the toes, is crucial for preserving the structure of the foot, supporting the arch, and absorbing shock. Overuse, trauma, or inflammation of the plantar fascia are the usual causes of plantar fasciitis. Plantar pain is the primary symptom, which is followed by stiffness, increasing pain, and an irregular gait.It is especially aggravated after waking up in the morning, prolonged standing, or exercise, and is relieved by walking a few steps or pulling. Conclusions:Plantar fasciitis is a sterile infection, with multiple factors influencing its clinical presentation. Its management requires a multidisciplinary approach that includes surgical treatment, pharmacologic management, physical factor therapy, and lifestyle changes. Early diagnosis, as well as appropriate treatment, is essential to optimize the patient’s prognosis and maintain physical function.